Weight stigma and bias: standards of care in overweight and obesity—2025 - Kamlesh Khunti; Leigh Perreault; Vanita R Aroda; Fatima Cody Stanford; Louis J Aronne; Kimberly A Gudzune; Scott Kahan; Raveendhara R Bannuru; Stephanie L Fitzpatrick; Nuha A ElSayed; Kirthikaa Balapattabi; Allison K Bennett; et al. (BMJ Open Diabetes Research & Care)
Weight bias involves negative attitudes and stereotypes towards individuals based on their weight, which can be explicit or implicit. This bias contributes to weight stigma, or the mistreatment and social devaluation of individuals based on weight. Weight stigma is linked to adverse physical and mental health outcomes, leading to reduced access and quality of healthcare for individuals with obesity. The American Diabetes Association (ADA)’s Obesity Association developed guidelines on recognizing and addressing weight bias and stigma. All healthcare professionals and staff should receive training on weight bias and stigma to improve care for individuals with obesity. Training should start early and continue throughout medical education and practice. Multicomponent training that combines education with hands-on learning is recommended to reduce explicit and implicit weight bias. Clinical practices, a potential source of stigmatization for people living with obesity, should be equipped with appropriate furniture and equipment to establish an inclusive environment. Privacy and sensitivity during anthropometric measurements are essential to minimize stigmatization. Healthcare professionals should use person-centered, non-judgmental language and engage individuals in shared decision-making to consider their health and goals. Asking permission to discuss weight and respecting individual preferences is crucial. The ADA’s Obesity Association encourages adopting these guidelines to reduce weight bias and stigma, emphasizing education, inclusive clinical environments, and effective communication to improve obesity care.